HUBUNGAN EFEKTIVITAS PEMBELAJARAN DARING, AKTIVITAS FISIK, DAN ASUPAN MAKRONUTRIEN DENGAN INDEKS PRESTASI KUMULATIF MAHASISWA S1 ILMU GIZI UPN VETERAN JAKARTA (ANGKATAN 2018 DAN 2019) - Camilia Lathifa Suseno (2021)
GPA is a student‟s pride in getting academic results that will determine the students things that have been mastered during lectures. Factors that can affect the GPA are the effectiveness of online class, physical activity, and macronutrient intake. The purpose of this study is to analyze the relationship between the effectiveness of online class, physical activity, and macronutrient intake with UPN Veteran Jakarta's S1 GPA of Nutrition Science students (batch 2018 and 2019). This research is an observational analytic study using a cross sectional approach. The population in this study were S1 Nutrition Science students of batch 2018 and 2019 with a total of 171 people. The sample to be used in this study was taken using a total sampling technique. The data were collected through filling out questionnaires boldly. The results showed that respondents who had bold enough effective learning, light physical activity, and less macronutrient intake. The research statistical test used the Chi-Square test. The results of statistical tests showed that there was a relationship between learning that dared physical activity, and intake of macronutrient carbohydrates and protein (P value = 0.000) with GPA. However, there was no relationship between fat intake and GPA (P value = 0.129).